Efektivitas Penggunaan Media Buku Saku dalam Pembelajaran Pendidikan Kewarganegaraan untuk Menumbuhkan Cinta Budaya Daerah Siswa (Studi Kuasi Eksperimen pada Siswa Kelas VII SMP Negeri 5 Malang) - Maya Mashita (MODELING: Jurnal Program Studi PGMI, 2016)
This study aims to determine effective use of instructional media pocket book on learning Civic Education to foster a culture of love student area. The approach used in this study is a quantitative approach with a quasi-experimental methods and research design is pretest and posttest control group. The study used a sample of students in grades 7.1 and 7.2 SMP Negeri 5 Malang. Instrument used in this study was a questionnaire, test, attitude scale, and performance tests. Data analysis technique used is Independent Samples Test. The results showed that: 1) there are differences in knowledge of the love of local culture significantly between the experimental class with a grade control, 2) there are differences in the attitude of the love of local culture significantly between the experimental class with a grade control, and 3) there are different skills love culture that significant between the experimental class with a grade control class.